TREATMENT OF CARDIOVASCULAR DISEASES - Qayumov Lazizjon Adiz o‘g‘li; Uraqova Shahlo Turdiyevna (TADQIQOTLAR, 2026)
Abstract.  Cardiovascular  diseases  (CVDs)  are  the  leading  cause  of  death worldwide and remain a major public health problem. This paper reviews the main aspects  of  CVDs,  including  risk  factors,  prevention,  and  treatment  methods.  The development  of  these  diseases  is  mainly  associated  with  hypertension,  diabetes, dyslipidemia,  smoking,  and  unhealthy  lifestyle.  Effective  management  includes lifestyle  modification,  pharmacological  therapy,  and,  in  severe  cases,  surgical  or interventional  procedures.  Recent  medical  advances  have  improved  treatment outcomes, but prevention and early diagnosis remain the most important strategies. Overall,  an  integrated  approach  is  essential  to  reduce  the  global  burden  of cardiovascular diseases.